Blockade of the AHR restricts a Treg-macrophage suppressive axis induced by L-Kynurenine - Campesato, Luis Felipe; Budhu, Sadna; Tchaicha, Jeremy; Weng, Chien-Huan; Gigoux, Mathieu; Cohen, Ivan Jose; Redmond, David; Mangarin, Levi; Pourpe, Stephane; Liu, Cailian; Zappasodi, Roberta; Zamarin, Dmitriy; et al. (Nature communications, 2020)
Tryptophan catabolism by the enzymes indoleamine 2,3-dioxygenase 1 and tryptophan 2,3-dioxygenase 2 (IDO/TDO) promotes immunosuppression across different cancer types. The tryptophan metabolite L-Kynurenine (Kyn) interacts with the ligand-activated transcription factor aryl hydrocarbon receptor (AHR) to drive the generation of Tregs and tolerogenic myeloid cells and PD-1 up-regulation in CD8 + T cells. Here, we show that the AHR pathway is selectively active in IDO/TDO-overexpressing tumors and is associated with resistance to immune checkpoint inhibitors. We demonstrate that IDO-Kyn-AHR-mediated immunosuppression depends on an interplay between Tregs and tumor-associated macrophages, which can be reversed by AHR inhibition. Selective AHR blockade delays progression in IDO/TDO-overexpressing tumors, and its efficacy is improved in combination with PD-1 blockade. Our findings suggest that blocking the AHR pathway in IDO/TDO expressing tumors would overcome the limitation of single IDO or TDO targeting agents and constitutes a personalized approach to immunotherapy, particularly in combination with immune checkpoint inhibitors. The tryptophan metabolite kynurenine is an endogenous ligand of the aryl hydrocarbon receptor (AHR). Here, the authors show that AHR targeting in IDO/TDO-expressing tumours counteracts a regulatory T cell/macrophage suppressive axis and synergizes with immune checkpoint blockade to hinder tumour growth.